1996
DOI: 10.1111/j.1095-8649.1996.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced oxygen level on the mortality and hatching rate of Chondrostoma nasus embryos

Abstract: Exposure of embryos of Chondrostoma nasus to a strongly reduced oxygen content (about 10% of air saturation) enhanced mortality and depressed hatching success. Viable larvae hatched only from the controls and from the group exposed to reduced oxygen during the earliest embryogenesis (from fertilization to gastrula). In the groups exposed from gastrula to eyed stage and from eyed stage to hatching, a high percentage of fish hatched, but all were deformed and almost all died during the following 1-5 days. Hatchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 9 publications
1
39
1
Order By: Relevance
“…A summarized comparison of the hatching period amplitude reached in our study with data known from literature (in relation to temperature) is given in Figure 4 (values presented by Watanabe et al (1948) and Wang et al (2008) serve as the reference figures for hatching in temperature range 25-30 °C in M. anguillicaudatus -we did not observe hatching in weatherfish at temperatures above 24 °C (due to lethal impact -see Discussion below)). Size of newly hatched larvae seems to be considerably influenced by parental attributes (Wootton, 1990;Panagiotaki and Geffen, 1992;Kamler, 2005), or water conditions (Keckeis et al, 1996;Prokes et al, 1998;Schiemer et al, 2003). We observed a significant decrease of the total length of newly hatched larvae (our data are c. 15% lower on average) compared to the figures presented by Grieb (1937), Kryzanovskij (1949), Kotlyarevskaja (1967) or Kostomarova (1975), probably caused by smaller egg size (observed during stripping -see Discussion above).…”
Section: Table III Total Length Of M Fossilis Larvae (Mean ± Sd) Acontrasting
confidence: 52%
See 2 more Smart Citations
“…A summarized comparison of the hatching period amplitude reached in our study with data known from literature (in relation to temperature) is given in Figure 4 (values presented by Watanabe et al (1948) and Wang et al (2008) serve as the reference figures for hatching in temperature range 25-30 °C in M. anguillicaudatus -we did not observe hatching in weatherfish at temperatures above 24 °C (due to lethal impact -see Discussion below)). Size of newly hatched larvae seems to be considerably influenced by parental attributes (Wootton, 1990;Panagiotaki and Geffen, 1992;Kamler, 2005), or water conditions (Keckeis et al, 1996;Prokes et al, 1998;Schiemer et al, 2003). We observed a significant decrease of the total length of newly hatched larvae (our data are c. 15% lower on average) compared to the figures presented by Grieb (1937), Kryzanovskij (1949), Kotlyarevskaja (1967) or Kostomarova (1975), probably caused by smaller egg size (observed during stripping -see Discussion above).…”
Section: Table III Total Length Of M Fossilis Larvae (Mean ± Sd) Acontrasting
confidence: 52%
“…Temperature is considered one of the most important ones, affecting development and growth (Penaz et al, 1983;Kamler et al, 1998;Green and Fisher, 2004), morphometric features plasticity (Stouracova et al, 1988;Penaz et al, 1989), maximum swimming speed (Green and Fisher, 2004) or sex determination (Conover and Kynard, 1981). Many of the recent studies focused on early development of fishes arised to predict population dynamics and life requests of the various species for the intents of fisheries management (Keckeis et al, 1996;Kamler et al, 1998;Klimogianni et al, 2004;Jordaan et al, 2006). Therefore a comprehension of temperature effect on the early fish ontogeny is crucial in process of understanding of fish egg and early ontogenetic stages distribution, dynamics and mechanisms of adaptation (Klimogianni et al, 2004) to the fluctuating environmental conditions in the floodplain area (Ward, 1998;Pekarik et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[78,79] [4,79]. Yet, given that 40% DO is comparatively low for natural seagrass meadows, and the exposure in our experiment was considerably longer than what is common in nature, this result shows that S. typhle is able to cope with brooding also at reduced O 2 levels.…”
Section: (C) Paternal Carementioning
confidence: 60%
“…The boreal Solea solea, a bottomliving flatfish shows levels of metabolic response similar to those of Mudskippers. Keckeis et al (1996) showed that reduced oxygen (10% air saturation) increased mortality and decreased hatching success in nase Chondrostoma nasus. (Rosenberg 1972).…”
Section: Hypoxiamentioning
confidence: 99%